Strategi Pengembangan Sosial Ekonomi Masyarakat Melalui Pariwisata di Nagari Terindah Pariangan Kabupaten Tanah Datar - Salsabilla Wilda Alifia; Dwi Pratiwi Wulandari (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
This research examines the strategies for socio-economic development through tourism in Nagari Terindah Pariangan, Tanah Datar Regency. This village holds a rich history and unique tourist attractions, acknowledged as one of the most beautiful villages in the world. Using SWOT analysis, the study identifies strengths such as job creation and increased income, weaknesses like low product prices, opportunities such as enhanced human resources and employment opportunities, and threats including the potential shift from agricultural land use. Positive impacts on the local economy, fair benefit distribution, and the significant role of tourism in government revenue are also revealed. This research contributes valuable insights for local government, village leaders, and the community to guide more effective tourism development efforts aimed at improving the well-being of the local population.